If it's not what You are looking for type in the equation solver your own equation and let us solve it.
8-5(3-2x)=30
We simplify the equation to the form, which is simple to understand
8-5(3-2x)=30
Reorder the terms in parentheses
8+(-15+10x)=30
Remove unnecessary parentheses
+8-15+10x=+30
We move all terms containing x to the left and all other terms to the right.
+10x=+30-8+15
We simplify left and right side of the equation.
+10x=+37
We divide both sides of the equation by 10 to get x.
x=3.7
| 2e+6-5e=-12 | | (-2x+1)(2x+1)-3=0 | | g=5ah | | -7+v=8 | | b+12=10 | | 7x+5=6+2x | | 14x-16=64-2x | | 5*5-11+9= | | 8x-10=974 | | 6x+33=741 | | 7x+5=768 | | 5a-45= | | 3x+2y=4y-3x | | (x+5)(x-2)+3(x+1)=0 | | 4h^2+6h-133=0 | | 3a+7a-a= | | 9=-2r+2 | | x:(x+1)+6(x+3)=4 | | a+6b-2c+4a-4b+5c= | | 6x+23=16x-23 | | 6x+23=16x+57 | | 4/3r-3=r+2/3-1/3r | | 2f-5g-6f-2g+4f+8g= | | -5+x/3=9 | | 3.5=12s-58 | | -18+x^2-10y-y^2=0 | | x^2=y^2+10y+18 | | 2x+5y+3= | | 1+2x=x-17 | | 5a-2+8a+7-6a-3= | | 6c+4d-5c+7d= | | 3a+2b+4a= |